VOCABULARY MASTERY AND GRAMMAR MASTERY IMPACT ON EFL HIGH SCHOOL STUDENTS’ READING COMPREHENSION - Ina Rizki Thatsani (Universitas Indraprasta PGRI, 2018)
This research aims to achieve empirical data and analyze the effect of vocabulary and grammar mastery towards students’ reading comprehension at state senior high school in South Jakarta. This research used the data analysis technique, and those were descriptive statistics, requirement analysis, normality test, linearity test, and test of hypothesis. The research was carried out at three classes from three state senior high schools in South Jakarta. The sample was 90 students. Data collection is completed by giving 30 questions for the vocabulary test, 30 questions for grammar test, and 30 questions for a reading comprehension test. Due to the result, it can be inferred that there are significant effects of vocabulary and grammar mastery altogether towards students’ reading comprehension.Keywords: vocabulary mastery; reading comprehension; grammar skills, foreign language learning